ITA: Innovation of Science and Environmental Learning Model in 21st Century based on HOTS - Ichsan, Ilmi Zajuli; Rahmayanti, Henita (International Journal for Educational and Vocational Studies, 2020)
Learning in the 21st century requires a learning innovation, especially in science and environmental learning. That's because solving various environmental problems requires students' abilities, one of which is Higher Order Thinking Skills (HOTS). The purpose of this research was to develop a learning model called ITA (Identify problems, Think and Write, Analysis and Argumentation). This research was conducted in March 2020. The method used in this research was research and development. Validation was carried out for 11 validators via Google form (online media), consisting of 5 learning experts and 6 science teachers. The results of the study showed that the ITA learning model was categorized as very valid with an average score of 3.52 which could be interpreted as an ITA learning model suitable for use in science and environmental learning. Other innovations to support the implementation of the ITA learning model can be developed to strengthen the use of the ITA learning model. This study concludes that the ITA learning model is suitable for use in science and environmental learning.